Microwave‐Assisted Domino Palladium Catalysis in Water: A Diverse Synthesis of 3, 3′‐Disubstituted Heterocyclic Compounds. Issue 19 (6th May 2018) - Ramesh, Karu; Basuli, Suchand; Satyanarayana, Gedu
Abstract : An environmentally benign microwave‐assisted domino [Pd]‐catalyzed reaction, for the efficient and diverse synthesis of 3, 3′‐disubstituted indolines, oxindoles, and dihydrobenzofurans, is presented. Significantly, water served as the sole green solvent and the strategy displayed an excellent functional‐group tolerance. Remarkably, the process was also amenable to unmasked functional groups and furnished the products, in very good to almost quantitative yields. Abstract : A domino [Pd]‐catalyzed synthesis of 3, 3′‐disubstituted indolines, oxindoles, and dihydrobenzofurans is devised under microwave irradiation from readily available starting materials by using water as the sole green solvent. The strategy presents an excellent functional‐group tolerance with broad substrate scope.